Implementing (un)fair procedures: containing favoritism when unequal outcomes are inevitable [dataset] - Schmidt, Robert J.; Trautmann, Stefan T. (Universität, 2021)
We study the selection of people when unequal payoffs are inevitable, but fair procedures are feasible, as in selecting one person from several can...